PENGARUH PEMOTONGAN TANGKAI METODE “CANGKEM BUAYA” TERHADAP PENINGKATAN KUALITAS TANDAN BUAH SEGAR - Aries Sukariawan; Muhammad Damara Damanik; Suroso Rahutomo (Jurnal Agro Fabrica, 2019)
The low percentage fruit set will impact on the percentage of fruit to bunch and weight of Bunch. Fruit set islow causing the formation of partenokarpi fruit/coat so that the harvest process is involved in loading, carryingand processing. To solve the problem, the management of post-harvest Bunis is necessary. Comparing the "V"(conventional) stem cutting, which is often referred to as the “Cangkem Kodok” (CK) as it is usually applied inthe plantation and the treatment of bunches (stalk) and base of bunches/stalks that have no fruit/ brondolancalled a “Cangkem Buaya" (CB). This research was conducted on oil palm plantation year 2015 planting in thePlantation of Bah Birung Ulu PTP. Nusantara IV. Five Month research time, namely in February-June year2019. This research uses a descriptive analysis method that is the primary data retrieval analyzed with Analysisof Variance (ANOVA) and then conducted advanced test using the smallest real difference (BNT) at 5% as wellas correlation of several parameters Observation. The results showed that the weight of the stem garbage wastewith a higher CB treatment compared with CK treatment and with the treatment of CB can save the garbagethat does not fit, transport and sports per bunch in Afdeling 1 by 5.59%, Afdeling 2 8.02% and Afdeling 37.63%. With the treatment of stem cutting and base of the fruit bunching (Brondolan) or called the treatment ofcrocodile hoe can increase the percentage of Fruit to a bunch average of 6%. The oil extraction were 27%.